Drilling to Decipher Long-Term Sea-Level Changes and Effects – A Joint Consortium for Ocean Leadership, ICDP, IODP, DOSECC, and Chevron Workshop - C. S. Fulthorpe; K. G. Miller; A. W. Droxler; S. P. Hesselbo; G. F. Camoin; M. A. Kominz (Scientific Drilling, 2008)
No abstract available. doi:10.2204/iodp.sd.6.02.2008